Effects of Sowing Dates on Grain Yield and Oil Content of rapeseed (Brassicacampestris var L. toria) Varieties in Middle Terai Region, Nawalparasi, Nepal - Khatiwada, M.P.; Chaudhary, N.K.; Sah, S.K.; Dutta, J.P. (Journal of Agriculture and Environment, 2021)
A field experiment was laid out in split-plot design with sowing date in the main plot and varieties in the sub-plot to determine the effects of sowing dates on growth, yield and oil content of rapeseed varieties. Four sowing dates 15 days apart set on October 13th, 28th, November 12th and 27th and four rapeseed varieties (Unnati, Preeti, Pragati and Local landrace) were used. The results revealed that the highest grain yield and oil content was obtained from the October 28th sowing date and it was statistically different from all other dates of sowing. On average, oil content was decreased by 5.75% and seed yield by 0.65 t/ha for every fortnight delay in sowing from October 28th sowing date. Highest yield and oil content was obtained from variety Preeti and it was statistically different from all other three varieties. Variety Preeti was the best yielding variety for October sowing date while variety Unnati was the best for November sowing date. Preeti is recommended to be sown on October 28th in middle terai area for optimum yield but under late sown condition, Unnati is preferred for obtaining the optimum yield.